A Double Loop Continuous-Time Adaptive Equalizer - Gimeno, Cecilia; Royo, Guillermo; Guerrero, Erick; Sánchez-Azqueta, Carlos; Aldea, Concepción; Celma, Santiago (Jornada de Jóvenes Investigadores del I3A, 2017)
This paper presents an adaptive equalizer for shorthaul gigabit optical communications. It includes two adaptation loops to compensate the changes in level and spectrum of the input signal. It consumes 29.3 mW for a 1.25 Gb/s signal, transmitted through a 50-m length 1-mm core SI-POF.